Spinal Anaesthesia as an Adjunct to General Anaesthesia for Laparoscopic Abdominoperineal Rectal Amputation - Antunes,Marisa; Baumgärtel,Aleksander; Gjessing,Petter Fosse; Ytrebø,Lars Marius (Journal of Pain Research, 2023)
Marisa Antunes,1 Aleksander Baumgärtel,2 Petter Fosse Gjessing,3 Lars Marius Ytrebø1 1Department of Anaesthesiology, University Hospital of North Norway and Institute of Clinical Medicine, Acute and Critical Care Research Group, UiT – the Arctic University of Norway, Tromsø, Norway; 2Institute of Clinical Medicine, Acute and Critical Care Research group, UiT – the Arctic University of Norway, Tromsø, Norway; 3Department of Digestive Surgery, University Hospital of North Norway and Institute of Clinical Medicine, Gastro Surgery Research group, UiT – the Arctic University of Norway, Tromsø, NorwayCorrespondence: Lars Marius Ytrebø, Department of Anaesthesiology, University Hospital of North Norway and Acute and Critical Care Research Group, UiT – the Arctic University of Norway, Tromsø, Norway, Tel +47 90788058, Fax +4777626192, Email lars.marius.ytrebo@unn.noBackground: Spinal anaesthesia as an adjunct to general anaesthesia may reduce postoperative pain and opioid consumption after laparoscopic abdominoperineal rectal amputation. We designed a randomized double blinded pilot study with two objectives: 1) to explore potential benefits of spinal anaesthesia as an adjunct to general anaesthesia and 2) to provide power and sample size estimations for potential differences between the groups. Primary outcome measures were postoperative pain and oral morphine equivalent (OMEq) consumption.Methods: Patients scheduled for elective laparoscopic abdominoperineal rectal amputation at the University Hospital of North Norway were randomised to spinal (n=5) or a sham spinal procedure (n=5). Numeric rating scale (NRS) and OMEq were monitored postoperatively for 72 h.Results: Age, sex, body mass index, and ASA were not significantly different between the groups. During surgery, patients in the spinal group received less remifentanil (p=0.06). NRS was lower in the spinal group 1 hr after admittance to the post-anaesthesia care unit (PACU) (p=0.06) and on the first postoperative day at 8 AM (p=0.03). OMEq ...